Synergistic Effect of Statins and Abiraterone Acetate on the Growth Inhibition of Neuroblastoma via Targeting Androgen Receptor - Hu, Zengchun; Cheng, Chuandong; Wang, Yue; Chen, Tianrui; Tu, Junhong; Niu, Chaoshi; Xing, Rong; Wang, Yang; Xu, Yinghui (Frontiers in Oncology, 2021)
Neuroblastoma is the most common extracranial neuroendocrine tumor in childhood. Although many studies have tried to ﬁnd effective treatments, there are still numerous limitations in current clinical targeted therapy. So, it is important to find new therapeutic targets and strategies from a new perspective. Our previous study reported that the androgen receptor (AR) promotes the growth of neuroblastoma in vitro and in vivo. Based on documentary investigation, we postulated that the AR–SCAP–SREBPs-CYP17/ HMGCR axis may regulate cholesterol and androgens synthesis and form a positive enhancement loop promoting NB progression. Clinical samples and Oncomine database analysis proved the activation of AR–SCAP–SREBPs-CYP17/HMGCR axis in neuroblastoma. The combination of inhibitors of HMGCR (statins) and CYP17A1 (abiraterone acetate) showed synergistic effect that significantly inhibited the proliferation and migration with decreased expression of related genes detected in vitro and in vivo suggesting the dual-targeted therapy had the potential to inhibit the progression of neuroblastoma in spite of its MYCN status. This study provides new ideas for clinical treatment of neuroblastoma with efficacy and reduced toxicity.